Bending-shear interaction of cold-formed stainless steel lipped channel sections. (April 2021) - Dissanayake, D.M.M.P.; Poologanathan, K.; Gunalan, S.; Tsavdaridis, K.D.; Wanniarachchi, K.S.; Nagaratnam, B.
Highlights: Bending-shear interaction of stainless steel lipped channels was investigated. FE models were developed for shear, bending, and interaction behaviours. Sections with aspect ratios of 1.5 and 2.0 behave under bending-shear interaction. Codified provisions are too conservative for a higher level of applied shear force. Proposed interaction equations provide accurate and consistent predictions. Abstract: The bending-shear interaction response of cold-formed stainless steel lipped channel sections has been given inadequate attention in the past. Therefore, this paper investigates the bending and shear interaction behaviour of cold-formed stainless steel lipped channel sections using numerical studies. Finite element (FE) models were developed and validated against the experimental results found in the literature for three-point and four-point loading tests of lipped channel sections of both cold-formed stainless steel and cold-formed steel. The elaborated FE results were used for a comprehensive parametric study that was conducted comprising 60 FE models of three-point loading simulations of stainless steel lipped channels with five different aspect ratios to study the shear response and the bending-shear interaction response. Another 12 FE models of four-point bending simulations were developed to study the bending response. The numerical results were analysed and it is found that the sections with aspect ratios of 1.5 and 2.0 are subjected to the interaction of bending and shear while there is no interaction effect observed in the sections with other aspect ratios. Eurocode 3 and American specifications interaction equations were then evaluated using the numerical results. These design provisions are found to be too conservative for a higher level of applied shear force. Therefore, revised design equations for bending and shear interaction were proposed aiming better prediction accuracy. Further, a statistical evaluation was conducted for the proposed interaction equations and results suggest improved and consistent predictions.